Arachne's Voice: Race, Gender and the Goddess. (September 2019) - Maya, Kavita
This article considers the issue of racial difference in the Goddess movement, using the mythological figure of Arachne, a skilful weaver whom the goddess Athena transformed into a spider, to explore the unequal relational dynamics between white Goddess feminists and women of colour. Bringing Goddess spirituality and thealogical metaphors of webs and weaving into dialogue with postcolonial and black feminist perspectives on the politics of voice, marginality and representation, the article points to some of the ways in which colonial narratives weave through Goddess feminism, including practices of silencing and the romanticization of racial difference. Ultimately, I argue that feminist spirituality must recognize and address structural inequality between white women and women of colour, or in other words, listen to Arachne's voice.